The effect of BaF2 concentration and particle size distribution on the luminescence efficiency of YAG:Ce3+ phosphors. (3rd August 2018) - Valiev, D; Han, T; Stepanov, S; Vaganov, V; Paygin, V
Abstract: Y3 Al5 O12 (YAG) phosphor powders doped with Ce 3+ concentration were synthesized by the solid-state reaction method with different of BaF2 flux concentration. Morphological characterization, photoluminescent properties and decay characteristics of YAG phosphor powders were studied. It was shown that BaF2 directly influenced on particle size distribution of YAG:Ce 3+ phosphor. It is necessary to have both large particles agglomerates (size more than 40 μ m) and small one (size less than 4 μ m) to obtain high energy efficiency in polydisperse YAG:Ce 3+ phosphors. It was evidenced, that the effect of both large and small agglomerates on energy efficiency is observed. The luminescence decay time for all investigated samples is significantly different in the spectral range 500 and 700 nm from τ  ∼ 60 to 80 ns, respectively.